Device Therapy and Arrhythmia Management in Left Ventricular Assist Device Recipients: A Scientific Statement From the American Heart Association. Issue 20 (14th May 2019) - Gopinathannair, Rakesh; Cornwell, William K.; Dukes, Jonathan W.; Ellis, Christopher R.; Hickey, Kathleen T.; Joglar, José A.; Pagani, Francis D.; Roukoz, Henri; Slaughter, Mark S.; Patton, Kristen K.
Abstract : Left ventricular assist devices (LVADs) are an increasingly used strategy for the management of patients with advanced heart failure with reduced ejection fraction. Although these devices effectively improve survival, atrial and ventricular arrhythmias are common, predispose these patients to additional risk, and complicate patient management. However, there is no consensus on best practices for the medical management of these arrhythmias or on the optimal timing for procedural interventions in patients with refractory arrhythmias. Although the vast majority of these patients have preexisting cardiovascular implantable electronic devices or cardiac resynchronization therapy, given the natural history of heart failure, it is common practice to maintain cardiovascular implantable electronic device detection and therapies after LVAD implantation. Available data, however, are conflicting on the efficacy of and optimal device programming after LVAD implantation. Therefore, the primary objective of this scientific statement is to review the available evidence and to provide guidance on the management of atrial and ventricular arrhythmias in this unique patient population, as well as procedural interventions and cardiovascular implantable electronic device and cardiac resynchronization therapy programming strategies, on the basis of a comprehensive literature review by electrophysiologists, heart failure cardiologists, cardiac surgeons, and cardiovascular nurse specialists with expertise in managing these patients. The structure and design of commercially available LVADs are briefly reviewed, as well as clinical indications for device implantation. The relevant physiological effects of long-term exposure to continuous-flow circulatory support are highlighted, as well as the mechanisms and clinical significance of arrhythmias in the setting of LVAD support.